Medical Treatment of Gastrointestinal Stromal Tumors: State of the Art and Future Perspectives - Apice, Gaetano; Milano, Amalia; Bruni, Giovanni S.; Iaffaioli, Rosario V.; Caponigro, Francesco (Reviews on Recent Clinical Trials, 2006)
Gastrointestinal Stromal Tumor (GIST) is the most common mesenchymal neoplasm of the gastrointestinal tract, and it is characterized by the occurrence, in > 90 % of cases, of a gain of function mutation in the c-kit protooncogene. STI-571 (imatinib mesylate), a selective KIT tyrosine kinase inhibitor, has changed the natural history of this disease, since it has shown high effectiveness in metastatic GIST, and it is currently under investigation also in the adjuvant and neoadjuvant setting. Mechanisms of resistance to imatinib mesylate include both de novo, and, more frequently, acquired resistance, which may occur after several months of drug administration and possibly depends, in most cases, upon an acquired second mutation. In order to overcome imatinib mesylate resistance, the addition of other drugs may be considered in patients who have less than an optimal response to imatinib mesylate monotherapy. Investigational agents that are being studied in this setting include the mammalian target of rapamycin (mTOR) inhibitor RAD 001 and the protein kinase C inhibitor PKC412. In addition, other KIT tyrosine kinase inhibitors with anti-VEGF receptor inhibitory activity, such as SU11248, PTK787/ZK787 and AMG 706, are currently being explored as second line monotherapy for imatinib mesylate-resistant GIST. Finally, another new drug, ecteinascidin (ET-743), that blocks cell cycle progression in G2/M phase through a p53-independent apoptotic mechanism, has shown important preclinical and clinical activity against a number of human solid tumors, including GIST.
Keywords: imatinib mesylate